Sana'a : A City Development Strategy - World Bank (Washington, DC, 2014)
Sana'a is located in an upland basin at an altitude of 2300 meters within a mountainous and semi-arid region of Yemen. Because of its high altitude, the city enjoys a moderate climate year around. The main rainy season is in summer. The nearest port is Hodeidah, roughly 250 kilometers away. Bound by mountains and steep slopes to the east and west, the city has few options but to expand primarily along its north and south axes within its basin. In September 2005 the Sana'a Local Council convened a workshop to initiate the city development strategy (CDS) process, in coordination with The World Bank and the Arab Urban Development Institute (AUDI). Funding and organizational aspects of the CDS were approved in October 2006 by the Cities Alliance, and the CDS process was launched under the leadership of H.E. the Minister of State and Mayor of Sana'a. This publication seeks to summarize the main outcomes of the studies, discussions, and strategic planning accomplished during Sana'a CDS process. Moreover, it aims to serve as a guide for the city's local economic development that is presented in a manner that is accessible to a broad audience.